The Impact of CSR Dimensions on Customer Participation Behaviour in Banking Industry of Pakistan - Mubushar, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
This papers examines the impact of Customer dimension of CSR, local community dimension of CSR, employee dimension of CSR, supplier dimension of CSR on customer participation behaviour. Data was collected from 453 banking customers of Pakistan. Smart PlS was used to test the measurement model and structural equation modelling technique was run to test the hypotheses. The study found that all corporate social responsibility initiatives have positive impact on customer participation behaviour. The customer dimension of CSR have more influence to for active participation of customers followed by the local community dimension of CSR, employee dimension of CSR and supplier dimension of CSR. This study covered all primary stakeholders under the head of stakeholders’ theory and highlighted the importance of supplier-oriented corporate social responsibility for customer participation behaviour due to end-users. This study also sheds the light that customers have been changing their role from passive participation to active participation.